Military veterans with mental health problems: a protocol for a systematic review to identify whether they have an additional risk of contact with criminal justice systems compared with other veterans groups - Haw, Sally (2012)
BACKGROUND: There is concern that some veterans of armed forces, in particular those with mental health, drug or alcohol problems, experience difficulty returning to a civilian way of life and may subsequently come into contact with criminal justice services and imprisonment. The aim of this review is to examine whether military veterans with mental health problems, including substance use, have an additional risk of contact with criminal justice systems when compared with veterans who do not have such problems. The review will also seek to identify veterans' views and experiences on their contact with criminal justice services, what contributed to or influenced their contact and whether there are any differences, including international and temporal, in incidence, contact type, veteran type, their presenting health needs and reported experiences. METHODS/DESIGN: In this review we will adopt a methodological model similar to that previously used by other researchers when reviewing intervention studies. The model, which we will use as a framework for conducting a review of observational and qualitative studies, consists of two parallel synthesis stages within the review process; one for quantitative research and the other for qualitative research. The third stage involves a cross study synthesis, enabling a deeper understanding of the results of the quantitative synthesis. A range of electronic databases, including MEDLINE, PsychINFO, CINAHL, will be systematically searched, from 1939 to present day, using a broad range of search terms that cover four key concepts: mental health, military veterans, substance misuse, and criminal justice. Studies will be screened against topic specific inclusion/exclusion criteria and then against a smaller subset of design specific inclusion/exclusion criteria. Data will be extracted for those studies that meet the inclusion criteria, and all eligible studies will be critically appraised. Included studies, both quantitative and qualitative, will then undergo stage-specific analysis and synthesis. The final stage will combine the findings of both syntheses to enable new understandings of why, how, and by how much, military veterans with mental health problems, including problematic drug and alcohol use, come into contact with the criminal justice system